Correlation between Platelet-to-Lymphocyte Ratio, Neutrophil-to-Lymphocyte Ratio and Burden of Thrombus with Disease Severity in Patients with Pulmonary Thromboembolism - Mammadova, Ayshan; Taşkaraca, Kübra; Jeyranova, Günel; Orujlu, Aysel; Tatlılıoğlu, Merve; Duygulu, Serra; Yalçınkaya, Zeynep; Allahverdiyeva, Seriyye; Gündoğdu, Onur; Kılıç, Atiye Cenay Karabörk; Özbek, Sevcihan Kesen; Erbaş, Gonca; Oğuzülgen, İ.Kıvılcım (Hämostaseologie, 2025)
High neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are markers of subclinical inflammation and have been associated with prognosis and mortality in many diseases. In this study, we evaluated the comparative value of NLR and PLR in identifying high mortality risk in patients hospitalized with acute pulmonary thromboembolism (PTE), and their relationship with the anatomical burden of thrombus.Patients who were followed up due to PTE were evaluated retrospectively. NLR and PLR were calculated from complete blood counts. The thrombus burden was assessed by the Qanadli score; based on the patients' archival computed tomography angiography images. Mortality prediction was based on an algorithm using the Pulmonary Embolism Severity Index, echocardiographic findings, and troponin levels.Three hundred-two PTE patients were included in the study. Median NLR, PLR, and Qanadli score values were higher in nonsurvivors, with NLR (8.4 [2.2–18.9]) vs. (3.1 [0.4–13.1]), PLR (317 [87.6–525.3]) vs. (124.4 [30–476.3]), and Qanadli scores (21 [3–26]) vs. (9 [1–28]), respectively (p < 0.001). We showed that setting a threshold value of >4.45 for NLR and >151.59 for PLR significantly predicts the high mortality-risk group. In the receiver operating characteristic analysis, when the threshold value for the Qanadli score distinguishing between low-risk and high-risk disease was set at 15.5, the sensitivity was calculated as 98.8% and the specificity was 94.9% (p = 0.001).This study showed that NLR, PLR, and Qanadli scores can provide essential contributions to the clinician's determination of the anatomical burden of thrombus and disease severity in PTE patients.
Keywords: pulmonary thromboembolism; neutrophil-to-lymphocyte ratio; platelet-to-lymphocyte ratio; Qanadli score; mortality risk; s-PESI